Structural characterization of the Chaetomium thermophilum TREX-2 complex and its interaction with the mRNA nuclear export factor Mex67:Mtr2 - Dimitrova-Paternoga, Lyudmila Nikolova; Valkov, Eugene; Aibara, Shintaro; Flemming, Dirk; McLaughlin, Stephen H.; Hurt, Ed; Stewart, Murray (Structure, 2015)
The TREX-2 complex integrates mRNA nuclear export into the gene expression pathway and is based on a Sac3 scaffold to which Thp1, Sem1, Sus1, and Cdc31 bind. TREX-2 also binds the mRNA nuclear export factor, Mex67:Mtr2, through the Sac3 N-terminal region (Sac3N). Here, we characterize Chaetomium thermophilum TREX-2, show that the in vitro reconstituted complex has an annular structure, and define the structural basis for interactions between Sac3, Sus1, Cdc31, and Mex67:Mtr2. Crystal structures show that the binding of C. thermophilum Sac3N to the Mex67 NTF2-like domain (Mex67NTF2L) is mediated primarily through phenylalanine residues present in a series of repeating sequence motifs that resemble those seen in many nucleoporins, and Mlp1 also binds Mex67:Mtr2 using a similar motif. Deletion of Sac3N generated growth and mRNA export defects in Saccharomyces cerevisiae, and we propose TREX-2 and Mlp1 function to facilitate export by concentrating mature messenger ribonucleoparticles at the nuclear pore entrance.